MicroRNA‐34a‐5p Promotes Joint Destruction During Osteoarthritis. Issue 3 (8th February 2021) - Endisha, Helal; Datta, Poulami; Sharma, Anirudh; Nakamura, Sayaka; Rossomacha, Evgeny; Younan, Carolen; Ali, Shabana A.; Tavallaee, Ghazaleh; Lively, Starlee; Potla, Pratibha; Shestopaloff, Konstantin; Rockel, Jason S.; et al.
Abstract : Objective: MicroRNA‐34a‐5p (miR‐34a‐5p) expression is elevated in the synovial fluid of patients with late‐stage knee osteoarthritis (OA); however, its exact role and therapeutic potential in OA remain to be fully elucidated. This study was undertaken to examine the role of miR‐34a‐5p in OA pathogenesis. Methods: Expression of miR‐34a‐5p was determined in joint tissues and human plasma (n = 71). Experiments using miR‐34a‐5p mimic or antisense oligonucleotide (ASO) treatment were performed in human OA chondrocytes, fibroblast‐like synoviocytes (FLS) (n = 7–9), and mouse OA models, including destabilization of the medial meniscus (DMM; n = 22) and the accelerated, more severe model of mice fed a high‐fat diet and subjected to DMM (n = 11). Wild‐type (WT) mice (n = 9) and miR‐34a–knockout (KO) mice (n = 11) were subjected to DMM. Results were expressed as the mean ± SEM and analyzed by t ‐test or analysis of variance, with appropriate post hoc tests. P values less than 0.05 were considered significant. RNA sequencing was performed on WT and KO mouse chondrocytes. Results: Expression of miR‐34a‐5p was significantly increased in the plasma, cartilage, and synovium of patients with late‐stage OA and in the cartilage and synovium of mice subjected to DMM. Plasma miR‐34a‐5p expression was significantly increased in obese patients with late‐stage OA, and in the plasma and knee joints of mice fed a high‐fat diet. In human OA chondrocytes and FLS, miR‐34a‐5p mimic increased key OA pathology markers, while miR‐34a‐5p ASO improved cellular gene expression. Intraarticular miR‐34a‐5p mimic injection induced an OA‐like phenotype. Conversely, miR‐34a‐5p ASO injection imparted cartilage‐protective effects in the DMM and high‐fat diet/DMM models. The miR‐34a–KO mice exhibited protection against DMM‐induced cartilage damage. RNA sequencing of WT and KO chondrocytes revealed a putative miR‐34a‐5p signaling network. Conclusion: Our findings provide comprehensive evidence of the role and therapeutic potential of miR‐34a‐5p in OA.